2007
DOI: 10.1002/ejoc.200700602
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Benzoazocines from Substituted Tetrahydroisoquinolines and Activated Alkynes in a Tetrahydropyridine Ring Expansion

Abstract: Tetrahydroisoquinolines underwent tandem piperidine ring enlargement in the presence of activated alkynes in acetonitrile or methanol, producing tetrahydrobenzo[d]azocines in high yields. (© Wiley‐VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2007)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…The preceding trends were further confirmed by experimental measurements of the p K a of two additional pairs of enamino ester-containing annulated medium-sized cyclic derivatives (Chart ), namely, β-CO 2 Me and α,β-(CO 2 Me) 2 derivatives of 4-ethyl-1,4,5,6,7,8-hexahydroazonino­[5,6- b ]­indole ( IIIa-b ) , and 3-ethyl-1,2,3,6-tetrahydro-8,9-dimethoxybenzo­[ d ]­azocine ( IVa-b ) . The hexahydroazonino­[5,6- b ]­indole scaffold III is a ring-expanded (azocine → azonine) analogue of I , whereas the dimethoxybenzo moiety in IV replaces the indole ring in II .…”
Section: Resultssupporting
confidence: 55%
“…The preceding trends were further confirmed by experimental measurements of the p K a of two additional pairs of enamino ester-containing annulated medium-sized cyclic derivatives (Chart ), namely, β-CO 2 Me and α,β-(CO 2 Me) 2 derivatives of 4-ethyl-1,4,5,6,7,8-hexahydroazonino­[5,6- b ]­indole ( IIIa-b ) , and 3-ethyl-1,2,3,6-tetrahydro-8,9-dimethoxybenzo­[ d ]­azocine ( IVa-b ) . The hexahydroazonino­[5,6- b ]­indole scaffold III is a ring-expanded (azocine → azonine) analogue of I , whereas the dimethoxybenzo moiety in IV replaces the indole ring in II .…”
Section: Resultssupporting
confidence: 55%
“…It was shown that tetrahydroisoquinolines with 1-phenyl substituents reacted with methyl propiolate and acetylacetylene to give the expected benzazocines in good yields. [17][18][19] As it turned out, 1,1-disubstituted tetrahydroisoquinolines, 1-methyland 1-benzyl-1-phenylethynyl-1,2,3,4-tetrahydroisoquinolines 1a-c reacted differently with activated terminal alkynes 2a,b in trifluoroethanol (Scheme 1). The reaction occurred rather quickly in this solvent at +7 1C.…”
mentioning
confidence: 99%
“…A different type of ring expansion was reported by Vokressensky et al, starting from α-aryltetrahydroisoquinolines 429 and 11 . The formation of the corresponding zwitterion and aryl-assisted dissociation of the C−N bond was followed by an intramolecular S N 1 substitution, leading to two-carbon ring-expanded products 430 (Scheme ).…”
Section: Aza-cope and Related Rearrangementsmentioning
confidence: 84%